A new species of Neoephemera McDunnough, 1925 (Ephemeroptera: Neoephemeridae) from North Carolina and Virginia - Holland, Victor B.; Beaty, Steven R.; Jacobus, Luke M. (Zootaxa, 2016)
Neoephemera eatoni sp. nov. is described based on nymphs, imagos, and eggs from North Carolina and Virginia, USA. Nymphs of the new species are associated only with hornleaf riverweed (Podostemum ceratophyllum) growing on the surfaces of cobbles and boulders in moderate to swift flows, at a depth of up to one meter. Life stages were associated by laboratory rearing. Nymphs of the new species are distinguished from other Nearctic Neoephemera by the following combination of characters: all legs are short and stout, with overall lengths subequal to each other; tibial and tarsal lengths are subequal on all legs; tarsal claws are sharply curved; anterolateral projections on the pronotum and mesonotum are reduced; and anterosubmedian tubercles are absent from the pronotum. Male and female imagos exhibit unique abdominal maculations; the anterior protuberance of the mesonotum is obovate; and distinct leg banding patterns are absent. Male imagos have the fore tibia at least 2× the length of mid and hind tibiae, and female imagos have all legs subequal in length. Our new species may be most closely related to N. youngi based on imagos of the two species each having a small spine posteromedially on abdominal tergum II and having annulated terminal filaments. An updated key to North American species is provided.